Design of a high-speed vacuum pump motor applying 6Phase and harmonic reduction - Hyung-Sub Han; In-Jun Yang; Do-Hyeon Choi; Seung-Heon Lee; Dong-Joo Kim; Won-Ho Kim (AIP Advances)
This paper proposes a vacuum pump motor capable of high-speed, high-torque operation as part of a domestic production strategy where high-speed operation is essential. It introduces a 6Phase motor, modified from the existing 3Phase motor, which reflects the increased voltage utilization characteristics of Multi Phase systems. By using a 6Phase motor, it is possible to reduce line voltage usage compared to conventional 3Phase motors and increase the base speed, thereby enabling high torque at high speeds. Additionally, the use of a 6Phase motor results in the generation of 3n-order harmonics in the line voltage, which do not occur in 3Phase motors. To address the increase in Total Harmonic Distortion (THD) caused by these 3n-order harmonics resulting in additional losses due to eddy current losses in permanent magnets and iron losses, the paper proposes a final model that applies tapering to the rotor.